ON THE GENERALIZED VARIATIONAL-LIKE INEQUALITY PROBLEMS FOR MULTIVALUED MAPPINGS - Farajzadeh, A.; Salahuddin, - (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this paper, two classes of generalized variational-like inequalities problems for multivalued mappings are introduced and then by using KKM technique and Kakutani-Fan-Glicksberg fixed point theorem the solvability of them are investigated when the mappings are relaxed η-α- -monotone. One can consider this paper the topological vector space version of reference [15].